The impact of fluticasone furoate/vilanterol on healthcare resource utilisation in the Salford Lung Study in chronic obstructive pulmonary disease. (March 2021) - Bakerly, Nawar Diar; Browning, Dominy; Boucot, Isabelle; Crawford, Jodie; McCorkindale, Sheila; Stein, Norman; New, John P.
Aim: The Salford Lung Study (SLS) in chronic obstructive pulmonary disease (COPD) was a randomised controlled trial evaluating the effectiveness and safety of initiating fluticasone furoate/vilanterol (FF/VI) 100/25 µg versus continuing usual care (UC) in patients with COPD and a history of exacerbations. Here, we investigate the impact of initiating FF/VI on healthcare resource utilisation (HRU) in SLS COPD. Methods: HRU and interventions were determined from patients' electronic health records. Annual rates of on-treatment all-cause and COPD-related secondary care contacts (SCCs) and primary care contacts (PCCs) for FF/VI versus UC were analysed using a general linear model. Costs were derived from national data sources. Results: Least-squares (LS) mean annual rates of all-cause (9.81 versus 9.36) and COPD-related (1.57 versus 1.48) SCCs were similar for FF/VI and UC, as were rates of all-cause hospitalisations (0.87 versus 0.82). Mean duration of hospital stay/patient was 4.5 and 4.2 days, respectively. COPD-related SCC mean total cost/patient was £484 FF/VI and £475 UC. LS mean annual rates of all-cause PCCs were significantly higher for FF/VI (21.20 versus 18.88 UC; p  < 0.001). LS mean annual rates of COPD-related PCCs were similar for FF/VI and UC (2.42 versus 2.46). All-cause PCC mean total cost/patient was £900 FF/VI versus £811 UC, but COPD-related PCC costs were similar (£116 versus £114). Direct COPD-related total medical costs/patient were significantly lower for FF/VI (LS geometric mean £806 versus £963 UC; p  < 0.001). Discussion: In patients with COPD and exacerbation history, FF/VI may represent a less costly alternative to current therapies. GlaxoSmithKline plc. study HZC115151; ClinicalTrials.gov NCT01551758. The reviews of this paper are available via the supplemental material section.